Tres tipos de abono orgánico en la reproducción de Eisenia foetida y calidad química del lombricompost en Zungarococha - Iquitos, Perú - 2019 - Guerra Acho, Paulina (2020)
The present research work was carried out in the National University of the Peruvian Amazon entitled three types of organic fertilizer in the reproduction of Eisenia foetida and chemical quality of vermicompost in Zungarococha - Iquitos, Perú - 2019.. 3 Proportions of cattle, pig and guinea manure were used, having as reference manure that can be found in the area. The evaluations were carried out after three months, in wooden boxes of 1m x 0.25m x 0.25m high, in plots of 0.5m2 in area and 28m2 in total area, which was indoors with a cement floor. The statistical design used was a Completely Random Design (DCA), the treatments under study were: T1 (20kg / 0.5m2 Bovine manure + 5 kilos of Gliricidia sepium + 500 earthworms), T2 (20kg / 0.5m2 Porcine manure + 5 kilos of Gliricidia sepium + 500 earthworms), and T3 (20kg / 0.5m2 guinea pig dung + 5 kilos of Gliricidia sepium + 500 earthworms), obtaining the following results The types of organic fertilizers used as food for earthworms (Eisenia foetida) do not they influenced the reproductive characteristics such as the number of eggs and number of adult worms. the T1 with which the best result was obtained. they did not influence the chemical quality of the vermicompost, such as pH, and Phosphorus (ppm). influenced the chemical quality of the earthworm, the content of Nitrogen (%), and organic matter (%) with T3 giving the best results and Potassium (ppm),